Osteoarthritis in Older Adults: Is More Emphasis on Managing and Mitigating its Stressful Ramifications, and Enhancing Coping, and Self Efficacy Cognitions Indicated? - Ray, Marks (Journal of Aging Research And Healthcare, 2024)
Efforts to mitigate or prevent painful disabling osteoarthritis have been pursued for more than a century with limited success. This current overview briefly summarizes how selected beliefs and behaviors, including coping and stress management approaches are potential mediators or moderators of osteoarthritis pain and its overall common adverse prognosis and outcome. Published data housed predominantly in PUBMED, PUBMED CENTRAL, SCIENCE DIRECT, and GOOGLE SCHOLAR sites and pertaining to selected aspects of the literature of current interest, cumulative results reported as of May 30, 2024, show a modest to strong rationale exists for considering the abovementioned factors in efforts to reduce pain and enable daily functions. Accordingly this line of research should be continued, and translated clinically without undue delay, especially in the face of increases in the aging population and osteoarthritis prevalence and undue suffering.
Keywords: Chronic Osteoarthritis; Coping; Older Adults; Pain; Self Efficacy; Stress